Dance of Dollars: State Funding Effects on Local Health Department Expenditures. Issue 2 (March 2022) - Viall, Abigail H.; Bekemeier, Betty; Yeager, Valerie; Carton, Thomas
Abstract : Objective: We examined changes in total local health department (LHD) expenditures in the state of Washington following introduction of a new state funding program to support core public health services and infrastructure. Methods: We used a pre/posttest design regression model to evaluate changes in LHD expenditures 1, 2, and 6 years into the new state program. To address potential endogeneity in the model, we repeated all 3 analyses using 2-stage least squares regression. Results: In the base case, overall spending among LHDs significantly increased with receipt of the new state funds in the first years of the program (2008 and 2009). However, those increases were not sustained over the longer term (2013). In subpopulation analyses, total LHD spending increased more among larger LHDs. Conclusions: Between 2006 and 2013, new state investments in core public health functions increased Washington State LHD expenditures in the short term, but those increases did not persist over time. For public health financial modernization efforts to translate into public health infrastructure modernization successes, the way new investments are structured may be as important as the amount of funding added. Abstract : Supplemental Digital Content is Available in the Text.